2011
DOI: 10.1002/jsfa.4716
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of salt stress in wheat seedlings by mammalian sex hormones

Abstract: MSHs could be used effectively to protect wheat seedlings from the destructive effects of salt stress by stimulating both enzymatic and non-enzymatic antioxidant mechanism and by promoting levels of osmotic protectants such as proline and sugars resulting in osmotic adjustment, carbon storage and radical scavenging in plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 34 publications
(71 reference statements)
4
29
0
5
Order By: Relevance
“…It has been reported that ES application has a protective effect on plants under oxida-tive stress [45], which is similar to the effect of brassinosteriods (BRs), plant-specific steroid hormones, structurally similar to ES, on plant abiotic stress responses [23]. Ex- Phenylpropanoids and flavonoids are not only required for normal plant growth and development but they also play an important role in protecting plants against various stresses, including pathogen attacks [48] [49].…”
Section: Estradiol Has a Negative Effect On The Phenylpropanoid-flavomentioning
confidence: 92%
“…It has been reported that ES application has a protective effect on plants under oxida-tive stress [45], which is similar to the effect of brassinosteriods (BRs), plant-specific steroid hormones, structurally similar to ES, on plant abiotic stress responses [23]. Ex- Phenylpropanoids and flavonoids are not only required for normal plant growth and development but they also play an important role in protecting plants against various stresses, including pathogen attacks [48] [49].…”
Section: Estradiol Has a Negative Effect On The Phenylpropanoid-flavomentioning
confidence: 92%
“…Despite the fact that MSHs act as endocrine disruptors in aquatic animals, a number of studies have demonstrated their beneficial effects on plants coping with abiotic stresses [3]- [9]. Progesterone, 17β-estradiol and androsterone applications mitigated the effects of salinity stress by enhancing germination rate, and root and shoot length in maize [6] and wheat seedlings [7]. The protective effect of MSHs has also been reported in the case of chilling and heavy metal stresses [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…Another androgen (androsterone) stimulated resistance to cold in maize plants, among others, by decreasing the membrane damage (also measured by electrolyte leakage) (Erdal 2012a). Improvement of the resistance to stress (for example, drought, salinity) through the application of AN and other androgens has also been reported by Janeczko and others (2012) and Erdal (2012b).…”
Section: Discussionmentioning
confidence: 68%